The Impact of the COVID-19 Lockdown Restrictions on Physical Activity Levels in European Adolescents: A Systematic Review and Meta-Analysis - Oâ€™Brien, Tanya; Lynch, Aileen (European Scientific Journal, ESJ, 2023)
Aim: To evaluate how the COVID-19 public health lockdown restrictions impacted the physical activity levels of European adolescents aged 10-19. Methodology: Databases searched included CINAHL Complete, Medline, APA PsycInfo, AMED, EMBASE, SPORTDiscus, Web of Science, and Cochrane Library. Search terms comprised database-specific synonyms of â€œPhysical Activityâ€ AND â€œCOVID-19â€ AND â€œAdolescentsâ€. Included studies compared continuous, quantitative pre-COVID and during-COVID physical activity measurements of healthy adolescents aged 10-19 living in the European Union. The references of relevant systematic reviews were hand-searched for pertinent studies. Included studies were independently appraised using the Newcastle Ottawa Scale for Cohort Studies followed by meta-analysis. Findings: 1397 studies were retrieved via database search and three further studies through hand searches. After removing duplicates, 898 articles were independently screened in Covidence by two reviewers, resulting in five included studies. Quality Assessment ratings were â€˜poorâ€™ (4/5) or â€˜fairâ€™ (1/5). Random effects meta-analysis demonstrated a significant decline in European adolescent physical activity levels, with a Standard Mean Difference of 0.44 (95% CI, 0.03, 0.84; P=0.005, 4 studies, n=2286). When analyzed by gender, a non-significant trend of decreased physical activity was found in both boys (0.43, 95% CI, -0.07, 0.93; P=0.09, 3 studies, n=1030) and girls (0.25, 95% CI, -0.33, 0.84; P=0.40, 3 studies, n=1017). Conclusion: These results validate concerns that the COVID-19 lockdowns significantly negatively impacted already-poor adolescent physical activity levels, which could lead to long-term adverse effects on this cohortâ€™s health and well-being. This research demonstrates the importance of interventions to encourage physical activity participation in this demographic.